A guide to the mammals of China - Smith, Andrew T., 1946-; Xie, Yan, 1967- (Princeton University Press, 2008)
Features a comprehensive guide to all species of mammals found in China. This reference guide describes the physical characteristics, geographic distribution, natural history, and conservation status of every species.